Poly[[(mu(3)-isonicotinato-kappa O-3:O:N)(triphenylphosphine-kappa P)silver(I)] ethanol solvate] - Sadeghi, O.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the crystal structure of {[Ag(C6H4NO2)(C18H15P)]center dot C2H6O}(n), the 4-pyridylcarboxylate ion binds to the phosphine-coordinated silver atoms through one of the two oxygen atoms of the carboxyl unit, and to a third phosphine-coordinate silver atom through the nitrogen atom of the aromatic ring, giving a distorted tetrahedral coordination at the metal atom. The mu(3)-bridging mode leads to a layer motif; the disordered ethanol molecules are linked to the free carboxyl oxygen atom by O-H center dot center dot center dot O hydrogen bonds.